Frizzled 7 drives amplification of cancer stem-cell subpopulations and the aggressiveness and poor differentiation of human hepatocellular carcinoma - Anaïs Lopez; Alexia Paturel; Nadim Fares; Floriane Pez; Guanxiong Wang; Patricia Gifu; Lydie Lefrançois; Jihed Chouaref; Pierre Saintigny; Janick Selves; Jean-Marie Peron; Michel Rivoire; et al. (PLoS ONE, 2025)
FZD7 is one of the key players in the subset of WNT-TGFβ-activated hepatocellular carcinomas (HCC), but the consequences of its abnormal expression on hepatocarcinogenesis remain to be better understood. Herein, we aimed to investigate the role of the FZD7-mediated signaling in immature phenotype and aggressiveness of HCC. Firstly, 499 human HCCs were used for clinical and molecular comparisons regarding the expression of FZD7 and stemness-associated markers. We showed that FZD7 overexpression was associated with poor differentiation and, in combination with CD133, predicted a poor outcome of patients with aggressive recurrence. Next, the impact of WNT3/FZD7 signaling on the differentiation of hepatic cells was assessed in HCC cell lines, as well in the non-transformed progenitor HepaRG cell line and in primary human hepatocytes, transduced with WNT3 and FZD7-expressing lentiviruses. We demonstrated that the ectopic expression of WNT3 and FZD7 inhibited the differentiation behavior of HepaRG cells and human primary hepatocytes, amplified the pool of EpCAM(+), CD90(+) and CD133(+) subsets of HCC cell lines, and increased their cancer stem cell features. Moreover, we found that WNT3/FZD7-mediated stemness properties of cancer cells were independent of the stemness-associated marker NANOG. In conclusion, we identified the FZD7(+)/CD133(+) signature as a potential prognosis marker and molecular therapeutic target, and we strengthened the hypothesis for the involvement of FZD7 in the enrichment of a cancer stem cell pool in HCC.